DEVELOPMENT OF ANTIBODY TO RALSTONIA SOLANACEARUM AND ITS APPLICATION FOR DETECTION OF BACTERIAL WILT - YADI SURYADI (SEAMEO BIOTROP, 2009)
The serological assay for the detection of bacterial wilt caused by Ralstonia solanacearum RSwas able to provide information regarding the presence of the pathogen in plant materials Theresearch is was aimed to develop polyclonal antibody PAb for RS detection Bacterial wholecells of RS isolates mixed with glutaraldehyde were used to immunize New Zealand femalewhite rabbit The titre of antibody in culture supernatant was 1 1024 The PAb developed froma ground nut RS isolates reacted with infected plant samples from various locations It was ableto detect RS antigen of crude extract and pure cultures from tomato and potato plant samples45 using dot blot ELISA however the minimum detectable concentration of RS antigen was 10cellsml The PAb obtained in this study is sensitive enough to detect RS isolates in routineserological assayKey words Bacterial wilt Ralstonia solanacearum antibody dot blot ELISA